Caracterização e associação com sintomas respiratórios do material particulado suspenso no ar: o caso de Colombo-Paraná - Braga, Darci Martins (2007)
Airborne particles in the atmosphere have important consequences for health, visibility, climate, and human welfare in general. The chronic exposure to particulates has been associated with increased rates of asthma and other respiratory sicknesses, like the pneumoconiosis that causes loss of lung function. Two important parameters should be taken in account in this context; the respirable fraction of submicrometric aerosol particles, and its composition , that can penetrate into the alveolus of the lungs, causing diseases. Colombo is a city near Curitiba (capital of Paraná states) with 200,000 inhabitants. Between 2000 and 2004, approximately 3 million ton of lime was produced in this city, this activity is important generator of aerosol particles. In the present research, aerosol particles were characterized in the central region of Colombo city, where concentrates lime industries. Samples were further analyzed for chemical and morphological aspects, determining the particle size distribution and classifying them according to elemental composition. By the application of the low-Z EPMA technique, the chemical composition of individual particles can be quantitatively elucidated, including low-Z components like C, N and O, as well as higher-Z elements. With this results, simulation of deposition in the respiratory system were performed. Information concerning the bulk composition is provided by EDXRF. Enrichment factor was calculated, showing that the aerosol particles founded were from anthropogenic source. Besides the analysis of aerosol particles, it was applied a questionnaire about respiratory diseases to the population that lives near the lime industries. Comparing to another population that lives far from the limes industries, it was founded more incidence of symptoms of respiratory diseases in those who lives near. Affecting more children, which reinforced the worry about the influence of the air quality to the population health of Colombo city.